Optimization of 4G LTE Network Bad Spot Area using Automatic Cell Planning Method - Yuhanef, Afrizal; Aulia, Siska; Jasmanto, Jasmanto (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2023)
The 4G LTE technology is widespread in almost all regions in Indonesia, including Solok City in West Sumatra, where this study was conducted. Based on the results of the 1800 MHz frequency drive test, the RSRP value was in the good category (81.44%), but the SINR value was in the poor category (56.96%). Furthermore, the results of the 2100 MHz frequency drive test showed that the RSRP value was in the poor category (58.11%), and the SINR value was also in the poor category (54.62%). These results indicate that the area had poor network quality. Therefore, this study aimed to optimize the Bad Spot Area in Solok City using the Automatic Cell Planning (ACP) method. The ACP method optimization results show that at the 1800 MHz frequency, the value of the ten cells is in the interval -127.84 ≤ RSRP ≤ -99.34. Meanwhile, at the 2100 MHz frequency, the value of the seven cells is in the poor category, which is in the interval -136.39 ≤ RSRP ≤ -111.03. In the 2100 MHz frequency, there is a decrease in RSRP value in the poor cate-gory from 43.27% to 41.85%. SINR parameter optimization results of 2100 MHz frequency, the percentage of a very good category is higher with a value of 51.40% than 44.16% at 1800 MHz frequency.